CURRENT STATE OF REGULATORY ENFORCEMENT OF CONSTITUTIONAL RIGHT OF CITIZENS TO PEACEFUL ASSEMBLY, WITHOUT WEAPONS, FREELY HOLD RALLIES AND DEMONSTRATIONS - Romanov, Maksym (Honor and Law, 2022)
The author analyzes the formation of the main national legal instruments of regulation of the institute of peaceful assembly, establishes the place and role in the legal regulation of the institute of international law and summarizes the general theoretical and practical conclusions on the possible optimization of the system of normative and legal ensuring implementation of constitutional right of citizens to assembly peacefully in Ukraine. The author comes to conclusions that the constitutional right of citizens to assembly peacefully, without weapons, hold rallies and demonstrations in Ukraine is one of the fundamental tools for participation in the management of public affairs for citizens. It is also argued that the historical foundations of the formation of Ukrainian statehood indicate that the citizens of Ukraine systematically exercise the right to peaceful assembly in all its possible forms. The author emphasizes the need to amend some legislative acts of Ukraine in connection with the regulation of the institution of peaceful assemblies (strengthening the responsibility for obstructing the organization of a peaceful assembly or intentional illegal restriction of such a meeting; to ensure public security and order in places of mass gatherings of citizens and others). The author argued that in the conditions of active use of the rights of citizens of Ukraine to peaceful assemblies, the issue of streamlining and legal regulation of its functioning is critical.